Disinfection and sterilization of endoscopic equipment: modern challenges and safety standards - V Pashynskyi; Y Radeha (Perioperative Medicine)
Endoscopic methods of diagnosis and treatment are critically important in modern medicine. At the same time, their use carries the risk of transmitting infections, especially due to insufficient processing of instruments. The article presents an analysis of modern approaches to disinfection and sterilization of endoscopes, the use of Spaulding’s classification, the use of some new technologies.